2005
DOI: 10.1038/nature03860
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent electrogenic chloride/proton exchange by endosomal CLC proteins

Abstract: Eukaryotic members of the CLC gene family function as plasma membrane chloride channels, or may provide neutralizing anion currents for V-type H(+)-ATPases that acidify compartments of the endosomal/lysosomal pathway. Loss-of-function mutations in the endosomal protein ClC-5 impair renal endocytosis and lead to kidney stones, whereas loss of function of the endosomal/lysosomal protein ClC-7 entails osteopetrosis and lysosomal storage disease. Vesicular CLCs have been thought to be Cl- channels, in particular b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
522
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(541 citation statements)
references
References 26 publications
17
522
2
Order By: Relevance
“…It is well established that ClC-4 and ClC-5 mediate coupled anion/proton antiport. 15,16 We therefore performed simultaneous voltage-clamp and fluorescence pH measurements in transfected cells, a methodology that we have previously applied to describe ClC-4 and ClC-5 transport. 28,39 Upon depolarization, significant alkalinization was observed in cells expressing ClC-3 13−19A (Figure 2a).…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that ClC-4 and ClC-5 mediate coupled anion/proton antiport. 15,16 We therefore performed simultaneous voltage-clamp and fluorescence pH measurements in transfected cells, a methodology that we have previously applied to describe ClC-4 and ClC-5 transport. 28,39 Upon depolarization, significant alkalinization was observed in cells expressing ClC-3 13−19A (Figure 2a).…”
Section: ■ Resultsmentioning
confidence: 99%
“…ClC-4 and ClC-5 mediate coupled Cl − /H + exchange across biological membranes. 15,16 For ClC-4 and ClC-5, a sufficient fraction of transporters inserts into the surface membrane allowing the application of standard electrophysiological techniques for functional studies. In contrast, surface expression of ClC-3 is too low 17,18 to allow unambiguous characterization of its transport characteristics.…”
mentioning
confidence: 99%
“…It is expressed in different cell types in vesicles of the endocytotic-lysosomal pathway; in osteoclasts, ClC-7 is localized also in the ruffled border and is involved in the acidification of the resorption lacuna. Recently it has been shown that, as previously suggested by work on bacterial ClC homologues, the ClC-7 protein and other members of the ClC family are not passive chloride ion channels, but rather secondary active chloride/proton antiporters (Accardi & Miller, 2004;Picollo & Pusch, 2005;Scheel et al, 2005;Graves et al, 2008;Zifarelli & Pusch, 2009).…”
Section: Introductionmentioning
confidence: 81%
“…Excepting very few cases, the OCRL mutations associated with Dent disease 2 do not overlap with those causing Lowe syndrome. 10,20,24 Missense mutations occur in the middle region of the gene (exons 9-15), whereas truncating mutations are found exclusively in the first 7 exons; the OCRL mutations associated with Lowe syndrome are located instead in the 3 0 region of the gene (exons [9][10][11][12][13][14][15][16][17][18][19][20][21][22] and involve all three functional OCRL1 domains, whereas frameshift and nonsense mutations cluster in exons [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The different distribution of OCRL mutations in Dent disease 2 and Lowe syndrome suggests a genotype-phenotype correlation that has yet to be thoroughly explored.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] It has recently been demonstrated, however, that ClC-5 functions as a Cl À/H þ antiporter when activated by positive voltages. 7,8 No CLCN5 gene mutations are detected in approximately 40% of patients with the classic symptoms of Dent's disease, suggesting a locus heterogeneity. The OCRL gene located on chromosome Xq26.1, whose mutations cause Lowe syndrome, has recently been found altered in 20% Dent's patients, 9 but about 20% of patients carry neither CLCN5 nor OCRL mutations.…”
Section: Introductionmentioning
confidence: 99%